ZnCl2/NaCl-Catalysed Hydrothermal Carbonization of Glucose and Oil Palm Shell Fiber - Teh, S.J.; Hamid, Sharifah Bee Abd; Lai, C.W.; Lim, Y.S. (American Scientific Publishers, 2015)
Advanced carbon nanomaterials are a class of materials of considerable research interest, as a cheaper alternative to expensive metals and composites. Plant biomass such as oil palm shell fiber (OPSF) is a renewable source of carbon for the production of advanced carbon nanomaterials. In the present study, two types of carbon-based precursors i.e., OPSF and glucose were treated via hydrothermal carbonization (HTC) method using a ZnCl2/NaCl catalyst mixture as chemical activator and for pore creation. The resultant samples were then analysed using Fourier transform infrared (FT-IR) spectroscopy, Raman spectroscopy, Brunauer-Emmett-Teller (BET) surface area analysis, and CHNS elemental analysis. Based on the results obtained, the lignocellulosic structure of OPSF underwent complete degradation in the presence of ZnCl2/NaCl catalyst mixture, coupled with the onset of nanographitic structure formation. The effect of the catalyst was more significant on the samples obtained from OPSF, due to the additional catalytic role of zinc chloride in the presence of nitrogen-containing structures in plant biomass. Further thermal annealing of HTC-treated OPSF revealed an interesting observation of amorphous carbon nanoparticles decorated with graphitized, 4-5 nm sized-carbon nanoparticles. BET surface analysis shows a large surface area up to 597.6 m2 g-1 was obtained from OPSF using the present method. The micropore volume was increased from 0.148 (Sample American B1) to 0.243 (Sample B3) cm3 g-1 with the addition of ZnCl2/NaCl catalyst. The adsorption isotherm indicated Type 1 adsorption-desorption behaviour, which corresponds to the formation of microporous structure in the carbon nanoparticles. Such a mechanistic understanding is important for the controlled growth of high content advanced carbon-based materials, which may be used in energy storage applications.